Pollution resistance and removal efficiency of mesophytic plants of polluted water bodies (Bangladesh Journal of Botany, 2024)
With the development of cities and economic growth, the eutrophication of urban park landscape water has become a hot topic in environmental governance and research at home and abroad. Using indoor water pollution simulation experiments, the decontamination and pollution resistance performance of six aquatic plants were studied. The research results found that all six aquatic plants can reduce the pH value of eutrophic water bodies. The pH of the Lythrum salicaria L. (Q) and Iris tectorum Maxim (Y) treatment systems was the lowest which are 7.34 and 7.48, respectively. They were significantly lower than the control group (CK). The content of nitrogen and phosphorus elements were reduced by six types of plants in the wastewater. After the completion of the experiment, the total nitrogen (TN) removal efficiency of Y was as high as 66.2%, and its content decreased from 9.49 to 3.21 mg/l. The removal rates of total phosphorus (TP) by six types of plants ranged from 59.1 to 81.3% and they were significantly higher than the CK. Among them, the removal rate of TP in wastewater by Y treatment exceeded 80%, which is superior to other plants and significantly different from CK. After the completion of the experiment, the content of chlorophyll a (chl a) in the water treated with Y was the lowest (6.6 mg/l). It was significantly lower than the other treatments (P